Respuesta :
Answer:
[tex]53g = 2g - 23g + 2 \\ 53g = - 21g + 2 \\ 53g + 21g = 2 \\ 74g = 2 \\ g = \frac{2}{74} \\ g = \frac{1}{37} \\ thank \: you[/tex]
[tex] \begin{cases}\large\bf{\red{ \implies}} \tt \: 53 \: g \: = \: 2 \: g \: - \: 23 \: g \: + \: 2 \\ \\ \large\bf{\red{ \implies}} \tt \: 53 \: g \: = \: - 21 \: g \: + \: 2 \\ \\ \large\bf{\red{ \implies}} \tt \: 53 \:g \: + \: 21 \: g \: = \: 2 \\ \\ \large\bf{\red{ \implies}} \tt \: 74 \:g \: = \: 2 \\ \\ \large\bf{\red{ \implies}} \tt \:g \: = \: \cancel\frac{2}{74} \\ \\ \large\bf{\red{ \implies}} \tt \: g \: = \: \frac{1}{37} \end{cases}[/tex]